Gambaran Pengetahuan Wanita Usia Subur Tentang Pemeriksaan Payudara Sendiri (SADARI) Di Wilayah Kerja Puskesmas Oesapa Tahun 2023 - Ninick Corea Fernandez; Ermi Lilianda Alang; Diah Ayu Dwi Satiti (Lembaga Pengembangan Kinerja Dosen, 2023)
Background: Breast cancer occurs when cells in the breast tissue grow uncontrollably and take over healthy breast tissue and its surroundings. The prevalence of breast cancer in Indonesia is 18/100,000 women. Riskesdas data for 2018 shows the prevalence of breast cancer in Indonesia is 61,682 cases. Based on the 2018 Riskesdas data, the prevalence of cancer in East Nusa Tenggara in 2018 was 1.49% or the equivalent of 44,782 cases. Purpose: The aim of this study was to determine the knowledge of women of childbearing age about breast self-examination (BSE) in the working area of the Oesapa Health Center. Methods: This research uses a descriptive research type. The sample in this study were 68 WUS in the working area of the Oesapa Health Center. Sampling technique with Proportional Random Sampling. Data analysis using frequency distribution. Results: The results of this study were then given an interpretation based on the variables studied based on the criteria of good, sufficient and lacking. The results of this study indicate that women of childbearing age in the working area of the Oesapa Health Center have less knowledge about BSE with a total of 27 people (39.7%), 25 people (36.8%) have sufficient knowledge and 16 people have good knowledge. Conclusion: Most of the knowledge of women of childbearing age about breast self-examination (BSE) is mostly in the less category.